Habitat of the amphibious mudskipper Periophtalmodon schlosseri in Songkhla Lake, Thailand (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Pattaratumrong MS, Pompha T. 2024. Habitat of the amphibious mudskipper Periophtalmodon schlosseri in Songkhla Lake, Thailand. Biodiversitas 25: 1875-1881. This study aimed to investigate the preferred habitat of giant mudskippers, Periophtalmodon schlosseri Pallas 1770. It was conducted from August to October 2022 at six sampling stations in Koh Yoh, a small island in the Lower Songkhla Lake. Environmental parameters such as organic matter and organic carbon in sediment, temperature, salinity, dissolved oxygen, and substrate were observed. The results indicate that the density of giant mudskipper weak to moderate correlates with all studied environmental parameters (P